Energy storage element

By optimizing the expansion rate and thickness of the electrode body in storage elements with uniaxially stretched separators, the issue of temporary resistance increase during high-current-density cycles is addressed, ensuring sustained performance.

JP7666012B2Active Publication Date: 2025-04-22GS YUASA CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021027573
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-24
Publication Date
2025-04-22
Estimated Expiration
2041-02-24

AI Technical Summary

Technical Problem

Electric storage elements with uniaxially stretched separators experience a temporary increase in resistance after repeated charging and discharging at high current densities, leading to deteriorated output performance due to the smaller expansion rate of hard carbon active material layers.

Method used

The storage element is designed with an electrode body where the positive and negative electrodes are superimposed via a uniaxially stretched separator, and the total expansion rate of the active material layers is kept at 5% or less when the separator is charged, ensuring a thickness of the electrode body in the charging state that is 0.95 or more relative to the internal dimensions of the container.

Benefits of technology

This configuration effectively suppresses the temporary increase in resistance after high-current-density charge and discharge cycles, maintaining the output performance of the storage element.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666012000005
    Figure 0007666012000005
  • Figure 0007666012000006
    Figure 0007666012000006
  • Figure 0007666012000007
    Figure 0007666012000007
Patent Text Reader

Abstract

To provide a power storage element arranged so that the temporary increase in resistance can be suppressed after a charge-discharge cycle with a high-current density, and which is small in active material layer's expansion coefficient when having been brought from a state of being discharged to a state of being charged.SOLUTION: A power storage element comprises: an electrode body 10 arranged by putting together cathodes 11a, 11b having cathode active material layers and anodes 12a, 12b having anode active material layers through corresponding separators 13; and a container 18 serving to contain the electrode body. A total expansion coefficient of the cathode active material layer and the anode active material layer when the power storage element has been brought from the state of being discharged to the state of being charged is 5% or less. The separator is a uniaxial extension separator. A thickness of the electrode body in the state of being charged is 0.95 or larger to an inside size of the container in a thickness direction of the electrode body.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an energy storage element. [Background technology]

[0002] Due to their high energy density, non-aqueous electrolyte secondary batteries, typified by lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc. In addition, as electricity storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors, electricity storage elements using electrolytes other than non-aqueous electrolytes, etc. are also widely used.

[0003] A typical energy storage element is one that includes an electrode assembly in which a positive electrode containing a positive electrode active material and a negative electrode containing a negative electrode active material are stacked with a separator interposed therebetween. Patent Document 1 describes a nonaqueous electrolyte secondary battery that includes a negative electrode that includes hard carbon. Patent Document 2 describes a battery that includes a positive electrode that includes a composite oxide containing lithium and nickel, and a separator that is formed by uniaxial stretching. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-162441 A [Patent Document 2] JP 2006-260906 A Summary of the Invention [Problem to be solved by the invention]

[0005] A negative electrode active material layer containing hard carbon (non-graphitizable carbon) has a smaller expansion rate when changing from a discharged state to a charged state than one containing graphite or the like. However, according to the study by the present inventors, a storage element including an electrode body in which an electrode having such an active material layer and a uniaxially stretched separator are combined is likely to have a temporary increase in resistance and a decrease in output performance after repeated charging and discharging at a high current density (high rate). Such a temporary increase in resistance and decrease in output performance are also called transient deterioration. To address such inconveniences, for example, graphite or the like may be used instead of hard carbon (non-graphitizable carbon) and a biaxially stretched separator may be used instead of the uniaxially stretched separator. However, in order to utilize the advantages of hard carbon (non-graphitizable carbon) and the uniaxially stretched separator, it is expected that the above-mentioned inconveniences can be improved without changing the active material and the separator.

[0006] An object of the present invention is to provide an energy storage element having an electrode body having a uniaxially stretched separator and in which the expansion rate of an active material layer when changing from a discharged state to a charged state is small, and in which a temporary increase in resistance after charge-discharge cycles at a high current density is suppressed. [Means for solving the problem]

[0007] An energy storage element according to one aspect of the present invention comprises an electrode body in which a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer are stacked with a separator interposed therebetween, and a container for accommodating the electrode body, wherein the total expansion coefficient of the positive electrode active material layer and the negative electrode active material layer when changing from a discharged state to a charged state is 5% or less, the separator is a uniaxially stretched separator, and the thickness of the electrode body in a charged state is 0.95 or more relative to the inner dimension of the container in the thickness direction of the electrode body. Effect of the Invention

[0008] According to one aspect of the present invention, it is possible to provide an energy storage element having an electrode body having a uniaxially stretched separator and an active material layer with a small expansion coefficient when changing from a discharged state to a charged state, in which a temporary increase in resistance after charge-discharge cycles at a high current density is suppressed. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view for explaining the thickness of an electrode assembly in a charged state, etc. [Diagram 2] FIG. 2 is a perspective view showing an energy storage element according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing an embodiment of an energy storage device formed by assembling a plurality of energy storage elements according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an overview of the energy storage element disclosed in this specification will be described.

[0011] An energy storage element according to one aspect of the present invention comprises an electrode body in which a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer are stacked with a separator interposed therebetween, and a container for accommodating the electrode body, wherein the total expansion coefficient of the positive electrode active material layer and the negative electrode active material layer when changing from a discharged state to a charged state is 5% or less, the separator is a uniaxially stretched separator, and the thickness of the electrode body in a charged state is 0.95 or more relative to the inner dimension of the container in the thickness direction of the electrode body.

[0012] The electric storage element according to one aspect of the present invention is an electric storage element having an electrode body with a small expansion rate of the active material layer during charging and a uniaxially stretched separator, and a temporary increase in resistance after a charge / discharge cycle at a high current density is suppressed. The reason for this is unclear, but the following reason is presumed. In a conventional electric storage element, if the electrodes (positive and negative electrodes) have wrinkles or the like, the distance between the electrodes becomes nonuniform, and it is considered that a temporary increase in resistance occurs due to uneven distribution of charged ions such as lithium ions that move between the positive and negative electrodes with repeated charge / discharge at a high current density. In particular, when the separator is a uniaxially stretched separator, the thickness of the uniaxially stretched separator is nonuniform compared to that of a biaxially stretched separator, so that the distance between the electrodes is easily nonuniform, and a temporary increase in resistance after a charge / discharge cycle at a high current density occurs significantly. In addition, when the expansion rate of the active material layer during charging is small, the change in the porosity of the active material layer during the charge / discharge cycle is small, and therefore the change in the amount of electrolyte present in the pores of the active material layer is small even during charge / discharge at a high current density. Therefore, when the uneven distribution of charged ions such as lithium ions occurs in the active material layer, this uneven distribution is difficult to eliminate, and a temporary increase in resistance is likely to occur. In contrast to such conventional energy storage elements, in the energy storage element according to one aspect of the present invention, the thickness of the electrode body in the charged state is set to 0.95 or more relative to the inner dimension of the electrode body in the thickness direction of the container, and a sufficient load is applied to the electrode body. Therefore, according to the energy storage element according to one aspect of the present invention, the distance between the electrodes is uniformed, and uneven distribution of charged ions such as lithium ions is unlikely to occur, and it is presumed that a temporary increase in resistance after a charge / discharge cycle at a high current density is suppressed. Note that, in the case where the separator provided in the energy storage element is a biaxially stretched separator, if the thickness of the electrode body in the charged state is set to 0.95 or more relative to the inner dimension of the electrode body in the thickness direction of the container, an increase in resistance due to pressing is likely to occur. The reason for this is presumed to be that, since biaxially stretched separators generally have lower compression resistance than uniaxially stretched separators, the separator is easily compressed when a load is applied to the electrode body, which causes an increase in resistance.In contrast, in the case of a uniaxially stretched separator, the separator has high compression resistance, so it is unlikely to be compressed in a way that would increase resistance when a load is applied to the electrode assembly. It is also presumed that the resistance may actually decrease due to the uniform distance between the electrodes, etc.

[0013] The "total expansion rate (X) of the positive electrode active material layer and the negative electrode active material layer when the discharged state is changed to the charged state" is a value obtained by the following method. The storage element is discharged at a constant current of 0.2C to SOC 0% to be in a discharged state. The storage element is disassembled, the positive electrode and the negative electrode are taken out, washed with dimethyl carbonate to remove the electrolyte salt contained in the positive electrode and the negative electrode, and dried under reduced pressure at room temperature for 24 hours or more, and then the thickness of the positive electrode active material layer and the thickness of the negative electrode active material layer are measured. These are respectively defined as the positive electrode active material layer thickness (A1) in the discharged state and the negative electrode active material layer thickness (B1) in the discharged state. The thickness of each active material layer is defined as the average value of the values ​​measured at any five points. In addition, when active material layers are provided on both sides of one positive electrode or negative electrode, the total thickness of the active material layers on both sides is defined as the thickness of the active material layer. Next, the removed positive electrode and negative electrode are used to assemble the storage element. The assembled storage element is charged at a constant current of 0.2C until the voltage reaches 100% SOC of the original storage element, and then charged at the same voltage. The total charging time is 8 hours. The storage element in this charged state is disassembled, the positive and negative electrodes are taken out, washed with dimethyl carbonate to remove the electrolyte salt contained in the positive and negative electrodes, and dried under reduced pressure at room temperature for 24 hours or more, after which the thickness of the positive electrode active material layer and the thickness of the negative electrode active material layer are measured. These are respectively the thickness of the positive electrode active material layer in the charged state (A2) and the thickness of the negative electrode active material layer in the charged state (B2). From these thicknesses, the total expansion coefficient (X) is calculated using the following formula.

[0014]

number

[0015] The "internal dimension of the electrode body in the thickness direction of the container" refers to the "length obtained by subtracting the thickness of the other members from the internal dimension of the electrode body in the thickness direction of the container" when there are other members (e.g., spacers) other than the electrode body and electrolyte in the internal dimension direction of the container in which the positive electrode, negative electrode, and separator are stacked. In addition, when the container has a portion with different internal dimensions, such as a recessed portion, the length of the portion with the smallest internal dimension length is referred to as the "internal dimension of the electrode body in the thickness direction of the container". The thickness of the electrode body and the thickness of the other members are the thickness in the direction in which the positive electrode, negative electrode, and separator are stacked, and are the thickness in the internal dimension direction of the container. That is, each of the above thicknesses is the thickness in the vertical direction of the energy storage element shown typically in FIG. 1. In addition, the "internal dimension of the electrode body in the thickness direction of the container" refers to the value in a state in which the container is not pressed and is empty.

[0016] The "thickness (T) of the electrode body in a charged state" is a value calculated by the following formula. Thickness of the electrode body in the charged state (T) = Thickness of the positive electrode other than the positive electrode active material layer (A0) × Number of positive electrode layers + Thickness of the positive electrode active material layer in the charged state (A2) × Number of positive electrodes having only a positive electrode active material layer facing the negative electrode + Thickness of the positive electrode active material layer in a discharged state (A1) × Number of positive electrodes having only a positive electrode active material layer that does not face a negative electrode + Thickness of negative electrode other than the negative electrode active material layer (B0) × Number of negative electrode layers + Thickness of negative electrode active material layer in charged state (B2) × Number of negative electrodes having only a negative electrode active material layer facing a positive electrode + Thickness of the negative electrode active material layer in a discharged state (B1) × Number of negative electrodes having only a negative electrode active material layer that does not face a positive electrode + Separator thickness (C0) × number of separator layers Here, the number of layers is the number at the position where the total number of layers of the positive electrode, negative electrode, and separator is maximum in the direction in which the positive electrode, negative electrode, and separator are stacked (the inner dimension direction in the thickness direction of the electrode body of the container: the vertical direction in FIG. 1). The positive electrode active material layer facing the negative electrode means that at least a part of the surface of the positive electrode active material layer faces the surface of the negative electrode via the separator. Similarly, the negative electrode active material layer facing the positive electrode means that at least a part of the surface of the negative electrode active material layer faces the surface of the positive electrode via the separator. In addition, a positive electrode having a positive electrode active material layer facing the negative electrode and a positive electrode active material layer not facing the negative electrode, i.e., a positive electrode having a positive electrode active material layer on one side facing the negative electrode and a positive electrode active material layer on the other side not facing the negative electrode, is counted as consisting of 1 / 2 positive electrode having only a positive electrode active material layer facing the negative electrode and 1 / 2 positive electrode having only a positive electrode active material layer not facing the negative electrode. Similarly, a negative electrode having a negative electrode active material layer facing the positive electrode and a negative electrode active material layer not facing the positive electrode, i.e., a negative electrode having a negative electrode active material layer on one side facing the positive electrode and a negative electrode active material layer on the other side not facing the positive electrode, is counted as consisting of 1 / 2 negative electrode having only a negative electrode active material layer facing the positive electrode and 1 / 2 negative electrode having only a negative electrode active material layer not facing the positive electrode.

[0017] For example, the electrode body 10 shown in FIG. 1 is composed of two positive electrodes 11 (11a, 11b), two negative electrodes 12 (12a, 12b), and three separators 13. The positive electrodes 11 and the negative electrodes 12 are alternately stacked with the separators 13 interposed therebetween. The positive electrode 11a has a positive electrode substrate 14 and positive electrode active material layers 15a, 15b stacked on both sides thereof, while the positive electrode 11b has a positive electrode substrate 14 and positive electrode active material layers 15c, 15d stacked on both sides thereof. The negative electrode 12a has a negative electrode substrate 16 and negative electrode active material layers 17a, 17b stacked on both sides thereof, while the negative electrode 12b has a negative electrode substrate 16 and negative electrode active material layers 17c, 17d stacked on both sides thereof. In this electrode body 10, the positive electrode 11a is a positive electrode having a positive electrode active material layer 15b facing the negative electrode (negative electrode 12a) and a positive electrode active material layer 15a not facing the negative electrode. The positive electrode 11b is a positive electrode having only positive electrode active material layers 15c, 15d facing the negative electrode (negative electrode 12a and negative electrode 12b). In addition, in this electrode body 10, the negative electrode 12a is a negative electrode having only negative electrode active material layers 17a, 17b facing the positive electrode (positive electrode 11a and positive electrode 11b). The negative electrode 12b is a negative electrode having a negative electrode active material layer 17c facing the positive electrode (positive electrode 11b) and a negative electrode active material layer 17d not facing the positive electrode. Such an electrode body 10 is accommodated in a container 18 having an inner dimension L. In FIG. 1, the positive electrode 11, the negative electrode 12, and the separator 13 are illustrated as being separated from one another in schematic manner, but in reality, they are stacked one on top of the other. The thickness T of the electrode assembly 10 in the charged state in FIG. Thickness T of the electrode body 10 in a charged state =2A0+3 / 2A2+1 / 2A1+2B0+3 / 2B2+1 / 2B1+3C0

[0018] It is preferable that a load of 0.1 MPa or more is applied to the electrode body in the thickness direction. In such a case, the load makes the distance between the electrodes more uniform, and the uneven distribution of charged ions such as lithium ions is less likely to occur, so that a temporary increase in resistance after charge / discharge cycles at a high current density is more suppressed. In addition, since the uniaxially stretched separator provided in the storage element has a relatively high compression resistance and is less likely to be compressed as described above, an increase in resistance due to compression of the separator caused by the application of a load is less likely to occur.

[0019] The load applied to the electrode body is a value measured by the following method. The thickness of the storage element in the pressed state is measured, and this thickness is defined as the storage element thickness when pressed. After releasing the pressed state, a load cell is attached to the surface (pressure surface) of the container that was pressing the storage element, and the storage element is pressed until the storage element thickness when pressed is reached. The value obtained by dividing the pressure force at this time by the area of ​​the pressure surface of the container is defined as the load applied to the electrode body. The area of ​​the pressure surface is defined as the area of ​​the positive electrode active material layer as viewed in the stacking direction of the electrode body (as viewed in the vertical direction in FIG. 1). The area of ​​the positive electrode active material layer is defined as the maximum area as viewed in the stacking direction of the electrode body, and for example, in a wound electrode body, it is defined as the area from the apex of one curved part of the positive electrode located at the outermost position to the apex of the other curved part.

[0020] The negative electrode active material layer preferably contains non-graphitic carbon. By using non-graphitic carbon as the negative electrode active material, the charge / discharge cycle performance, high-rate discharge performance, etc. of the storage element can be improved. On the other hand, since non-graphitic carbon has a small expansion coefficient during charging, when the negative electrode active material layer of the storage element contains non-graphitic carbon, the advantage that a temporary increase in resistance after a charge / discharge cycle at a high discharge density is reduced can be particularly effectively obtained.

[0021] "Non-graphitic carbon" refers to the average lattice spacing (d 002) is 0.34 nm or more and 0.42 nm or less. Here, "fully discharged state of negative electrode active material" means a state in which the negative electrode active material carbon material is discharged so that charged ions such as lithium ions that can be absorbed and released during charging and discharging are sufficiently released. For example, in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, it is a state in which the open circuit voltage is 0.7 V or more.

[0022] Hereinafter, the energy storage element according to one embodiment of the present invention, the configuration of the energy storage device, the manufacturing method of the energy storage element, and other embodiments will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0023] <Electricity storage element> The electric storage element according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, an electrolyte, and a container for accommodating the electrode assembly and the electrolyte. The electrode assembly is formed by stacking a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer with a separator interposed therebetween. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are stacked with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are stacked with a separator interposed therebetween and wound. The electrolyte exists in a state of being impregnated in the positive electrode, the negative electrode, and the separator. As an example of an electric storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as a "secondary battery") will be described.

[0024] (positive electrode) The positive electrode has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer.

[0025] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by the volume resistivity being 10 or less, as measured in accordance with JIS-H-0505 (1975). 7The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H4160 (2006).

[0026] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, even more preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, the strength of the positive electrode substrate can be increased while increasing the energy density per volume of the secondary battery. The "average thickness" of the positive electrode substrate and the negative electrode substrate described later refers to the value obtained by dividing the punched mass when a substrate of a predetermined area is punched out by the true density and punched area of ​​the substrate.

[0027] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0028] The positive electrode active material layer contains a positive electrode active material and, as necessary, optional components such as a conductive agent, a binder, a thickener, and a filler.

[0029] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Ni γ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ)O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.

[0030] In addition, the above-mentioned lithium transition metal composite oxides having an α-NaFeO2 crystal structure, lithium transition metal composite oxides having a spinel crystal structure, and polyanion compounds can be suitably used as positive electrode active materials having a relatively small expansion coefficient during charging. Among these, the lithium transition metal composite oxides having an α-NaFeO2 crystal structure and the lithium transition metal composite oxides having a spinel crystal structure are particularly preferred in terms of high energy density, etc.

[0031] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0032] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.

[0033] The content of the positive electrode active material in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material in the above range, both high energy density and manufacturability of the positive electrode active material layer can be achieved.

[0034] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphitized carbon, non-graphitized carbon, graphene-based carbon, and the like. Examples of non-graphitized carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the shape of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. In addition, these materials may be used in a composite form. For example, a material in which carbon black and CNT are composited may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0035] The content of the conductive agent in the positive electrode active material layer is preferably 1 mass % or more and 10 mass % or less, and more preferably 3 mass % or more and 9 mass % or less. By setting the content of the conductive agent in the above range, the energy density of the secondary battery can be increased.

[0036] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0037] The content of the binder in the positive electrode active material layer is preferably from 1% by mass to 10% by mass, and more preferably from 3% by mass to 9% by mass. By setting the content of the binder in the above range, the active material can be stably held.

[0038] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.

[0039] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.

[0040] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0041] The positive electrode can be produced, for example, by applying a positive electrode mixture paste directly or via an intermediate layer to a positive electrode substrate and drying it. After drying, pressing or the like may be performed as necessary. The positive electrode mixture paste contains each component constituting the positive electrode active material layer, including a positive electrode active material and optional components such as a conductive agent and a binder. The positive electrode mixture paste usually further contains a dispersion medium.

[0042] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.

[0043] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbonaceous materials, etc. are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0044] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the secondary battery.

[0045] The negative electrode active material layer contains a negative electrode active material. The negative electrode active material layer contains optional components such as a conductive agent, a binder, a thickener, a filler, etc., as necessary. The optional components such as a conductive agent, a binder, a thickener, a filler, etc. can be selected from the materials exemplified for the positive electrode above.

[0046] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0047] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; and Li4Ti5O 12 , LiTiO 2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitizable carbon or non-graphitizable carbon). In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0048] "Graphite" refers to graphite that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0049] Examples of non-graphitic carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0050] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0051] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0052] As the negative electrode active material, non-graphitic carbon is preferred, and non-graphitizable carbon is more preferred. When such a negative electrode active material is used, it has an advantage that the charge / discharge cycle performance and high-rate discharge performance of the secondary battery can be improved. The lower limit of the content of non-graphitic carbon relative to all the negative electrode active materials contained in the negative electrode active material layer is preferably 50 mass%, more preferably 70 mass%, and even more preferably 90 mass%. The negative electrode active material contained in the negative electrode active material layer may be substantially composed of non-graphitic carbon only. In such a case, the total expansion rate of the positive electrode active material layer and the negative electrode active material layer when the discharged state is changed to the charged state usually tends to be 5% or less. In addition, examples of negative electrode active materials with a small expansion rate during charging include titanium-containing oxides in addition to non-graphitic carbon.

[0053] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0054] The negative electrode can be produced, for example, by applying a negative electrode mixture paste directly or via an intermediate layer to a negative electrode substrate and drying it. After drying, pressing or the like may be performed as necessary. The negative electrode mixture paste contains each component constituting the negative electrode active material layer, including a negative electrode active material and optional components such as a conductive agent, a binder, and a thickener. The negative electrode mixture paste usually further contains a dispersion medium.

[0055] (Total expansion rate of positive electrode active material layer and negative electrode active material layer) The upper limit of the total expansion rate of the positive electrode active material layer and the negative electrode active material layer when the secondary battery is changed from a discharged state to a charged state is 5%, and may be 3% or 1%. When the total expansion rate is small like this, the advantages of the secondary battery are particularly effectively obtained because a temporary increase in resistance after a charge / discharge cycle at a high current density tends to be significant in a conventional energy storage element. The lower limit of the total expansion rate may be 0%. The total expansion rate can be adjusted by the type and content of the active materials in the positive electrode active material layer and the negative electrode active material layer.

[0056] (Separator) The separator is a uniaxially stretched separator, and can be appropriately selected from known uniaxially stretched separators. The uniaxially stretched separator has an advantage that it is difficult to shrink in a direction perpendicular to the stretching direction because it is stretched in only one direction. In addition, when a uniaxially stretched separator is used, it has an advantage that the resistance is unlikely to increase even when a load is applied to the secondary battery and the electrode assembly.

[0057] As the uniaxially stretched separator, for example, a uniaxially stretched separator consisting of only a substrate layer, a uniaxially stretched separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both sides of the substrate layer, etc. can be used. The uniaxially stretched separator may be one in which the substrate layer is formed by uniaxial stretching. That is, the substrate layer of the separator may be a porous resin film stretched uniaxially. Usually, the substrate layer of the uniaxially stretched separator is formed by a dry method. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferable from the viewpoint of shutdown function, and polyimide and aramid are preferable from the viewpoint of oxidation decomposition resistance. A material in which these resins are combined may be used as the substrate layer of the separator. The substrate layer may be composed of two or more layers.

[0058] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the energy storage element.

[0059] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0060] (Non-aqueous electrolyte) The nonaqueous electrolyte may be appropriately selected from known nonaqueous electrolytes. The nonaqueous electrolyte may be a nonaqueous electrolyte solution. The nonaqueous electrolyte solution includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.

[0061] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.

[0062] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.

[0063] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.

[0064] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0065] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0066] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0067] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3 More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0068] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; ethylene sulfite, propylene sulfite, dimethyl sulfite, and propane sulfite. sultone, propene sultone, butane sultone, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, tetrakistrimethylsilyl titanate, lithium monofluorophosphate, lithium difluorophosphate, and the like. These additives may be used alone or in combination of two or more.

[0069] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.

[0070] (Structure of the energy storage element, thickness of the electrode body relative to the inner dimensions of the container, etc.) The energy storage element according to one embodiment of the present invention is usually a square battery. FIG. 2 shows an energy storage element 1 having a wound electrode body as an example of a square battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a square container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51. The container 3 is a square container having a substantially rectangular parallelepiped shape. The container 3 may be a conventionally known container made of resin or metal. In the energy storage element 1 of FIG. 2, a pressing member (not shown) or the like may be provided to, for example, sandwich both sides of the container 3 (usually the thickness direction of the electrode body, the front side and the back side in FIG. 2) and press the container 3 and the electrode body 2 housed in the container 3 in the Y direction in FIG. 2.

[0071] The thickness of the electrode body 2 in the charged state is 0.95 or more, preferably 0.97 or more, and more preferably 0.99 or more, relative to the inner dimension of the electrode body 2 in the thickness direction of the container 3. As a result, the energy storage element 1 has an electrode body 2 having a small expansion rate of the active material layer during charging and a uniaxially stretched separator, while suppressing a temporary increase in resistance after charge / discharge cycles at a high current density. In the energy storage element 1 of FIG. 2, the thickness of the electrode body 2 and the inner dimension of the container 3 are the lengths in the Y direction in FIG. 2. In addition, the thickness of the electrode body 2 in the charged state may be 1.1 or less, 1.05 or less, or 1.0 or less, relative to the inner dimension of the electrode body 2 in the thickness direction of the container 3.

[0072] (Applying a load to the electrode body) The electrode body is preferably loaded in the thickness direction (vertical direction in FIG. 1, Y direction in FIG. 2). The lower limit of the pressure to apply a load to the electrode body is preferably 0.1 MPa, more preferably 0.3 MPa, and even more preferably 0.5 MPa. In such a case, the distance between the electrodes is made more uniform, and a temporary increase in resistance after charge / discharge cycles at a high current density is further suppressed. The upper limit of the pressure to apply a load to the electrode body may be, for example, 5 MPa or 3 MPa.

[0073] The load may be applied to the electrode body by pressing the container. Usually, the container is pressed, so that the load is also applied to the electrode body, but a part of the electrode body (for example, a pair of curved surfaces in a flat wound electrode body) may not be applied with the load. In addition, the load may be applied only to a part of the flat part of the laminated electrode body and the flat wound electrode body, for example, only to the central part.

[0074] The container can be pressed by providing, for example, a pressurizing member or the like. The pressurizing member may be a restraining member that restrains the shape of the container. The pressurizing member (restraining member) is provided, for example, so as to sandwich and press the container from both sides in the thickness direction (the vertical direction in FIG. 1, the Y direction in FIG. 2). Examples of the pressurizing member include a restraining band and a metal frame. For example, the metal frame may be configured so that the load can be adjusted by a bolt or the like. Also, a plurality of energy storage elements may be arranged side by side in the thickness direction, and fixed using a frame or the like in a state in which the plurality of energy storage elements are pressed from both ends in the thickness direction.

[0075] In the energy storage element of this embodiment, a temporary increase in resistance after a charge / discharge cycle at a high current density is suppressed, and therefore the energy storage element of this embodiment is suitable for use in applications where charging / discharging is performed at a high current density, such as power sources for automobiles such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs).

[0076] <Configuration of the power storage device> The energy storage element of this embodiment can be mounted as an energy storage device (battery module) configured by assembling a plurality of energy storage elements 1 in a power source for an automobile such as an EV, HEV, or PHEV, a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, the technology of the present invention may be applied to at least one energy storage element included in the energy storage device.

[0077] 3 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 1, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects two or more energy storage elements 1, a bus bar (not shown) that electrically connects two or more energy storage units 20, and the like. The energy storage unit 20 or the energy storage device 30 may include a state monitoring device (not shown) that monitors the state of one or more energy storage elements. The energy storage unit 20 or the energy storage device 30 may be provided with a pressure member (restraint member) such as a frame (not shown).

[0078] <Method of manufacturing the energy storage element> The manufacturing method of the energy storage element of the present embodiment can be appropriately selected from known methods. The manufacturing method includes, for example, preparing an electrode body, preparing a non-aqueous electrolyte, and housing the electrode body and the non-aqueous electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween. The manufacturing method may further include attaching a pressure member or the like.

[0079] <Other embodiments> The energy storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and a part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, a part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0080] In the above embodiment, the case where the storage element is used as a chargeable and dischargeable non-aqueous electrolyte secondary battery (e.g., a lithium ion secondary battery) has been described, but the type, shape, size, capacity, etc. of the storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors. The storage element of the present invention can also be applied to storage elements in which the electrolyte is an electrolyte other than a non-aqueous electrolyte. EXAMPLES

[0081] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0082] [Example 1] (Preparation of positive electrode) Positive electrode active material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode mixture paste was prepared using O2, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the positive electrode active material, AB, and PVDF was 90:5:5 (solid content conversion). The positive electrode mixture paste was applied to both sides of aluminum foil as a positive electrode substrate and dried. Then, roll pressing was performed to obtain a positive electrode.

[0083] (Preparation of negative electrode) A negative electrode mixture paste was prepared by mixing the negative electrode active material non-graphitizable carbon (HC), the binder styrene-butadiene rubber (SBR), the thickener carboxymethyl cellulose (CMC), and the dispersion medium water. The mass ratio of HC, SBR, and CMC was 98:1:1 (solid content conversion). The negative electrode mixture paste was applied to both sides of copper foil as the negative electrode substrate and dried. Then, roll pressing was performed to obtain a negative electrode.

[0084] The thickness of the positive electrode active material layer in the discharged state of the obtained positive electrode was 70.7 μm, and the thickness of the positive electrode active material layer in the charged state was 70.7 μm. The thickness of the negative electrode active material layer in the discharged state of the obtained negative electrode was 71.4 μm, and the thickness of the negative electrode active material layer in the charged state was 72.1 μm. The total expansion rate of the positive electrode active material layer and the negative electrode active material layer when the discharged state was changed to the charged state was 0.5%.

[0085] (electrolyte) A 1:1:1 volumetric mixture of propylene carbonate, dimethyl carbonate, and ethyl methyl carbonate was added to the solvent, and the resulting solution was diluted with 1.2 mol / dm 3 LiPF6 was dissolved in the electrolyte at a concentration of 0.01g / L to obtain an electrolyte.

[0086] (Separator) The separator used was a uniaxially stretched separator made of a three-layer polyolefin (PP / PE / PP) microporous membrane with a polyethylene (PE) layer between two polypropylene (PP) layers.

[0087] (Battery Assembly) A flat wound electrode body was obtained using the positive electrode, negative electrode, and separator. The thickness of the electrode body was adjusted by the number of turns so that the thickness of the electrode body in a charged state was 0.95 with respect to the inner dimension of the electrode body in the thickness direction of the container. The electrode body was housed in a square container, and an electrolyte was injected and sealed. A pressure member was attached, and the container was pressed in the thickness direction of the electrode body by this pressure member to obtain the storage element of Example 1. The load applied to the electrode body, determined by the above method, was 1.0 MPa.

[0088] [Examples 2 and 3, Comparative Examples 1 and 2, Reference Examples 1 to 3] The energy storage elements of Examples 2 and 3, Comparative Examples 1 and 2, and Reference Examples 1 to 3 were obtained in the same manner as in Example 1, except that the type of negative electrode active material and the thickness of the electrode body in a charged state relative to the inner dimension of the electrode body in the thickness direction in the container were as shown in Table 1. In Table 1, "HC" represents non-graphitizable carbon, and "Gr" represents graphite. In Example 3 and Comparative Example 2, a mixture of HC and Gr in a mass ratio of 1:1 was used as the negative electrode active material. The thickness of the negative electrode active material layer in the discharged state of the obtained negative electrode was 80.3 μm, and the thickness of the negative electrode active material layer in the charged state was 85.0 μm. The total expansion rate of the positive electrode active material layer and the negative electrode active material layer when changing from the discharged state to the charged state was 3.1%. The thickness of the negative electrode active material layer in the discharged state was 79.5 μm, and the thickness of the negative electrode active material layer in the charged state was 90.0 μm in the negative electrodes obtained in Reference Examples 1 to 3. The total expansion rate of the positive electrode active material layer and the negative electrode active material layer when changing from a discharged state to a charged state was 7.0%.

[0089] [evaluation] (Resistance change rate after high current density charge / discharge cycles) For each of the energy storage elements of Examples 1 to 3, Comparative Examples 1 and 2, and Reference Examples 1 to 3, the rate of resistance change after high current density charge / discharge cycles was measured by the following method. At 25°C, the storage element was charged at a constant current of 4A to 4.1V, then charged at a constant voltage of 4.1V until the total charging time reached 3 hours, and then discharged at a constant current of 4A to 2.4V, and the discharge capacity at that time was taken as Q1. The current value when discharging this discharge capacity Q1 in 1 hour was taken as 1C. The storage element in a discharged state (SOC0%) was adjusted to SOC50% by charging at 0.5C at 25°C for 1 hour. The storage element was discharged at 20C for 10 seconds, and the resistance before the charge-discharge cycle was calculated using the following formula (1). Resistance = {(Voltage before current is applied) - (Voltage at 10 seconds)} / Current (1) The storage element was adjusted to SOC 50% again. At 25°C, 1000 charge / discharge cycles were performed, with one cycle consisting of continuous discharge at 15C for 30 seconds and continuous charge at 15C for 30 seconds. No rest time was provided between charge and discharge. One hour after the end of the charge / discharge cycle, the storage element after the charge / discharge cycle was discharged at 20C for 10 seconds, and the resistance after the charge / discharge cycle was calculated using the above formula (1). The resistance before the charge / discharge cycle was D1, and the resistance after the charge / discharge cycle was D2, and the resistance change rate after the high current density charge / discharge cycle was calculated using the following formula (2). The results are shown in Table 1. Resistance change rate (%) = (D2 / D1) × 100 (2)

[0090] [Table 1] [Examples 4 and 5, Comparative Example 3, Reference Examples 4 to 6] The energy storage elements of Examples 4 and 5, Comparative Example 3, and Reference Examples 4 to 6 were obtained in the same manner as in Example 1, except that the type of separator, the thickness of the electrode body in a charged state relative to the inner dimension of the container in the thickness direction of the electrode body, and the presence or absence of pressing against the container were as shown in Table 2. When pressing was "present," the load applied to the electrode body was 0.1 MPa.

[0091] [evaluation] The resistance change rate after high current density charge / discharge cycles was calculated by the above-mentioned method for each of the energy storage elements of Examples 4 and 5, Comparative Example 3, and Reference Examples 4 to 6. The results are shown in Table 2.

[0092] [Table 2] [Examples 6 and 7, Comparative Examples 4 and 5, Reference Examples 7 to 10] The energy storage elements of Examples 6 and 7, Comparative Examples 4 and 5, and Reference Examples 7 to 10 were obtained in the same manner as in Example 1, except that the type of separator, the thickness of the electrode body in a charged state relative to the inner dimension of the container in the thickness direction of the electrode body, and the presence or absence of pressing against the container were as shown in Table 3. When pressing was "present," the load applied to the electrode body was 1.0 MPa.

[0093] [evaluation] For each of the energy storage elements of Examples 6 and 7, Comparative Examples 4 and 5, and Reference Examples 7 to 10, the resistance before the charge-discharge cycle was determined in the same manner as described in the above "Rate of Resistance Change After High Current Density Charge-Discharge Cycle". The results are shown in Table 3. In addition, the ratio of the resistance before the charge-discharge cycle was determined by comparing the energy storage elements that differ only in whether or not the container was pressed, and is shown in Table 3.

[0094] [Table 3] As shown in Table 1, in the energy storage element (Examples 1 to 3, Comparative Examples 1 and 2) in which the separator is a uniaxially stretched separator and the total expansion rate of the positive electrode active material layer and the negative electrode active material layer when changing from a discharged state to a charged state is 5% or less, it is found that by setting the thickness of the electrode body in the charged state to the inner dimension of the electrode body in the thickness direction of the container to 0.95 or more, the resistance change rate after the high current density charge / discharge cycle is small, that is, a temporary increase in resistance after the charge / discharge cycle at high current density is suppressed. Also, in the energy storage element (Reference Examples 1 to 3) in which the total expansion rate of the positive electrode active material layer and the negative electrode active material layer when changing from a discharged state to a charged state exceeds 5%, it is found that the problem of a temporary increase in resistance after the charge / discharge cycle at high current density does not substantially occur, regardless of the size of the thickness of the electrode body in the charged state to the inner dimension of the electrode body in the thickness direction of the container. As shown in Table 2, even when the separator is a biaxially stretched separator (Reference Examples 4 to 6), regardless of the thickness of the electrode body in the charged state relative to the inner dimension of the electrode body in the thickness direction of the container and regardless of the presence or absence of a load applied to the electrode body, it can be seen that there is substantially no problem of a temporary increase in resistance occurring after charge / discharge cycles at a high current density. In contrast, when the separator is a uniaxially stretched separator (Examples 4 and 5, Comparative Example 3), it can be seen from Table 2 that the temporary increase in resistance after charge / discharge cycles at a high current density is suppressed by setting the thickness of the electrode body in the charged state relative to the inner dimension of the electrode body in the thickness direction of the container to 0.95 or more and further applying a load to the electrode body. Furthermore, as shown in Examples 6 and 7 in Table 3, when the separator is a uniaxially stretched separator and the thickness of the electrode assembly in the charged state relative to the inner dimension of the electrode assembly in the thickness direction in the container is 0.95 or more, it can be confirmed that the resistance decreases when a load is applied to the electrode assembly. This tendency differs from the cases where the thickness of the electrode assembly in the charged state relative to the inner dimension of the electrode assembly in the thickness direction in the container is less than 0.95 (Comparative Examples 4 and 5, Reference Examples 7 and 8) and when the separator is a biaxially stretched separator (Reference Examples 7 to 10). [Explanation of symbols]

[0095] 10 Electrode body 11(11a, 11b) Positive electrode 12(12a, 12b) negative electrode 13 Separator 14 Positive electrode substrate 15a, 15b, 15c, 15d positive electrode active material layer 16 Negative electrode substrate 17a, 17b, 17c, 17d negative electrode active material layer 18 Container 1 Energy storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. An electrode body in which a positive electrode having a positive electrode active material layer and a negative electrode having a negative electrode active material layer are stacked with a separator interposed therebetween; and A container for accommodating the electrode assembly Equipped with the negative electrode active material layer contains non-graphitic carbon, a total expansion coefficient of the positive electrode active material layer and the negative electrode active material layer when the positive electrode active material layer is changed from a discharged state to a charged state is 5% or less; the separator is a uniaxially stretched separator, An energy storage element, wherein the thickness of the electrode body in a charged state is 0.95 or more relative to an inner dimension of the container in the thickness direction of the electrode body.

2. The energy storage element according to claim 1 , wherein a load of 0.1 MPa or more is applied to the electrode body in a thickness direction.

Citation Information

Patent Citations

  • Battery positive plate, flexible package lithium carbon fluoride primary battery and preparation method of flexible package lithium carbon fluoride primary battery

    CN111769253A

  • Lithium secondary battery

    JP2000173667A

  • Organic electrolyte battery

    JP2002313330A

  • Battery

    JP2006260906A

  • Wound cell

    JP2008027867A